The Role of Teachers in Developing Social Skills of Early Childhood Students at PAUD Shihabul Musthofa Merangkak, Embung Kandong Village, Academic Year 2024/2025 - Suhaini; Marniati (Journal of Education, Teaching, and Learning, 2025)
This study aims to analyze the roles and strategies of teachers in developing the social skills of early childhood learners at PAUD Shihabul Musthofa, as well as to identify supporting factors and challenges faced during the learning process. The study employs a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results reveal that the teacher's role in developing children's social skills falls into the "very good" category, with an observation score achievement of 81.25%. The teacher’s role includes lesson planning, implementing interactive activities, providing direct guidance, modeling social behavior, and reinforcing positive social attitudes. The strategies applied consist of learning through play, role-playing, habituation of social values, group work, and structured observation of children’s social behavior. Supporting factors for success include teachers’ strong understanding, parental involvement, and the support of school leadership. The main challenges encountered involve limited play facilities, the absence of formal training, and the diversity of children’s individual characters. This research highlights the importance of collaboration among teachers, parents, and school stakeholders in promoting the social development of early childhood learners through contextual and enjoyable learning strategies.